EFFICIENCY OF IMPLEMENTING SANCTIONS IN CASE OF POLYGAMY IN THE MODERN ISLAMIC WORLD - M. Samson Fajar; Abdul Qadir Jaelani (Transpublika Publisher, 2022)
Reform of family law is necessary, and this has become a trend in the renewal of Islamic family law in the modern world. One of the themes studied is the application of legal sanctions (criminalization). Criminalization is a product of modern law, which is very different from the fiqh law, which refers to society. In this study, polygamy is the theme that will be discussed. How is the implementation of criminal sanctions in cases of polygamy in some modern Muslim countries? The country objects that are the focus of the study are Indonesia, Malaysia, and Tunisia. The study approach uses a comparative approach, including vertical comparison (state law-classical legal doctrine), horizontal comparison (Law between countries), diagonal comparison (level of legal dynamics). Results in two conclusions that polygamy as a study of Islamic family law is a private matter and a public issue, so it requires firmness of sanctions. There are two views that polygamy law is prohibited and allowed with conditions, as for those who prohibit it, Tunisia by imposing criminal sanctions and those who allow it on condition that Indonesia and Malaysia, by imposing light sanctions.